In Utero Exposure to Bisphenol A Shifts the Window of Susceptibility for Mammary Carcinogenesis in the Rat - Betancourt, Angela M. (National Institute of Environmental Health Sciences, 2010)
BACKGROUND: Bisphenol A (BPA) is a ubiquitous environmental chemical with reported endocrine-disrupting properties. OBJECTIVE: Our goal in this study was to determine whether prenatal exposure to BPA predisposes the adult rat mammary gland to carcinogenesis. METHODS: Pregnant rats were treated orally with 0, 25, or 250 μg BPA/kg body weight (BW) from gestation day (GD) 10 to GD21. For tumorigenesis experiments, prenatally exposed female offspring received a single gavage of 7,12-dimethylbenz(a)anthracene (DMBA; 30 mg/kg BW) on postnatal day (PND) 50, or PND100. RESULTS: Prenatal exposure of the dam to 250 μg BPA/kg BW combined with a single exposure of female offspring to DMBA on PND100, but not on PND50, significantly increased tumor incidence while decreasing tumor latency compared with the control group. Prenatal exposure of the dam to 250 μg BPA/kg BW, in the absence of DMBA to the female offspring, increased cell proliferation and elicited differential effects at the protein level at PND100 compared with PND50. Differentially regulated proteins in the mammary gland included estrogen receptor-α, progesterone receptor-A, Bcl-2, steroid receptor coactivators, epidermal growth factor receptor, phospho-insulin-like growth factor 1 receptor, and phospho-Raf. CONCLUSIONS: Our study demonstrates that oral prenatal exposure to BPA increases mammary cancer susceptibility in offspring and shifts the window of susceptibility for DMBA-induced tumorigenesis in the rat mammary gland from PND50 to PND100. These changes are accompanied by differential effects of prenatal BPA exposure on the expression of key proteins involved in cell proliferation.